Abuse of medications for the treatment of migraines: results of an online survey - Nadezhda A. Koval'chuk; Anait E. Shagbazian; Giuzial R. Tabeeva (ZAO "Consilium Medicum", 2021)
Background. The abuse of headache medications is an important factor in the formation of drug-induced headache. Aim. To determine the prevalence and nature of drug use among patients with migraine and chronic cephalgic syndrome. Materials and methods. An Internet survey was conducted among 1598 Internet users, as well as through social networks (Instagram, Facebook, VK) using Google Forms. Results. 60% of respondents with chronic headache and migraine symptoms did not have a reliable diagnosis. More than 70% of patients choose a drug for pain relief on their own and 62.7% take the drug in every headache attack. Conclusion. Among patients with chronic headaches and migraines, there is a high percentage of people abusing symptomatic drugs, which indicates a high risk of drug-induced headache formation.